Effects of gymnastics training on physical function in children - Sheerin, K.; Williams, S.; Hume, P.; Whatman, C.; Gleave, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study assessed the effects of one hour per week of gymnastics training over 9 weeks on seven physical function variables in children aged 4-9. Of the total 205 children measured pre-gymnastics training, 41 boys and 62 girls completed post-testing measurements. Pre- to post-intervention change scores showed there were beneficial effects for the 30-s sit-up test for abdominal strength (17% increase), sit and reach test for lumbar and hamstring flexibility (6.4% increase), plate tapping test for upper limb speed and coordination (5.8% improvement), and vertical jump test for lower limb power (4.6% increase). The tables of age and gender normative ranges produced should be helpful for practitioners conducting similar physical function testing of children 4-9 years.